Symptom vs context: lessons learned from a large-scale implementation of the Cultural Formulation Interview - Silvius, Linda; Antezana J., Katrina V.; Ghane, Samrad (Frontiers in Psychiatry, 2024)
Mental health services in multicultural societies require culturally sensitive approaches to reduce health disparities. The Cultural Formulation Interview (CFI) is thought to enhance shared decision making and to facilitate culturally and contextually informed treatment. There is, however, little known regarding its implementability in large-scale psychiatric services. The current paper reports on (a) efforts to implement the CFI in a large organization for mental health services in the Netherlands, and (b) two studies that evaluated this implementation process and identified barriers to CFI adoption in clinical practice. Implementation of the CFI was facilitated by developing an online course, an advanced training of "team coaches", (digital) resources, and integrating the CFI question into the intake format. A preliminary evaluation revealed that the CFI was administered in only 13.2% of all intakes across the entire organization, with minimal utilization of training resources. Study 1 aimed to investigate how the CFI was perceived by clinicians and stakeholders. A survey of 150 clinicians found a great lack of familiarity with the CFI and its purpose. While 67% reported partial CFI use, 50% saw no added value, and 61% deemed it relevant only for ethnic minorities. Study 2 examined which patient and clinician variables were associated with adequate CFI use (i.e., correct documentation of the CFI information in initial intake reports). The sample consisted of 112 intakes of patients conducted by ten clinicians.Regression analysis showed a significant association between clinicians' cultural competences and adequate CFI use, meaning that more culturally competent clinicians tended to generate better cultural assessments using the CFI. In addition, the CFI information was documented more adequately among patients who were unemployed at the time of assessment. In conclusion, implementation of the CFI requires a fundamental rethinking of the entire intake assessment, shifting it from a symptom-oriented approach towards a context-and person-centered one. Future trainings may benefit from embedding the CFI within a broader cultural competency training, rather than solely focusing on the CFI, which is currently the common practice.